To simplify the expression \((r - 1)(r^2 - 2r + 3)\), we will use the distributive property (also known as the FOIL method for binomials).
-
Multiply \(r\) with each term in the second polynomial: \[ r \cdot r^2 = r^3 \] \[ r \cdot (-2r) = -2r^2 \] \[ r \cdot 3 = 3r \]
-
Now multiply \(-1\) with each term in the second polynomial: \[ -1 \cdot r^2 = -r^2 \] \[ -1 \cdot (-2r) = 2r \] \[ -1 \cdot 3 = -3 \]
-
Now combine all the results: \[ r^3 - 2r^2 + 3r - r^2 + 2r - 3 \]
-
Combine like terms: \[ r^3 + (-2r^2 - r^2) + (3r + 2r) - 3 \] \[ = r^3 - 3r^2 + 5r - 3 \]
Putting it all together, the simplified expression is: \[ \boxed{r^3 - 3r^2 + 5r - 3} \]